The Prevalence of Theileria spp. of Goat in Watthana Nakhon District, Sa Kaeo Province - แก้วหอม ไพทูล; ฐิตะสาร วรรณา (Journal of Mahanakorn Veterinary Medicine, 2018)
Theileriosis is a disease caused by Theileria spp. that infects both red and white blood cells of livestock animal such as cattle, buffalo, goat, and sheep. Theileria parasites have been reported as very pathogenic, causing a high ration of mortality in small ruminants, which can cause severe economic loss in animal husbandry. Therefore, it is necessary to check the epidemiology of Theileria spp. of livestock animal. The objective of this study was to investigate the prevalence of Theileria spp. of goat in Watthana Nakhon district, Sa Kaeo province. Blood samples of 196 goats were collected from 3 areas of Watthana Nakhon district including Huai Chot and Nong Waeng and Tha Kwian sub-district. The V4 region of 18S rRNA gene was amplified by polymerase chain reaction (PCR). The results demonstrated that the PCR product was approximately 230 bps in length. The prevalence of Theileria spp. infection in goat of Huai Chot, Nong Waeng and Tha Kwian sub-district was 32.70% (34/104), 57.50% (23/40), and 46.15% (24/52), respectively. The overall prevalence of Theileria spp. infection in goat of Watthana Nakhon district was 41.33% (81/196). In addition, the factors of location, and timing of blood collection affected the prevalence of Theileria spp. In summary, PCR technique can be used to determine the prevalence. The goats in Watthana Nakhon district were relatively high infected of Theileria spp. probably due to the farmers not to focus on the prevention and elimination of disease vectors.